Analysis of Adsorbate–Adsorbate and Adsorbate–Adsorbent Interactions to Decode Isosteric Heats of Gas Adsorption. Issue 18 (17th November 2015) - Madani, S. Hadi; Sedghi, Saeid; Biggs, Mark J.; Pendleton, Phillip
Abstract: A qualitative interpretation is proposed to interpret isosteric heats of adsorption by considering contributions from three general classes of interaction energy: fluid–fluid heat, fluid–solid heat, and fluid—high‐energy site (HES) heat. Multiple temperature adsorption isotherms are defined for nitrogen, T =(75, 77, 79) K, argon at T =(85, 87, 89) K, and for water and methanol at T =(278, 288, 298) K on a well‐characterized polymer‐based, activated carbon. Nitrogen and argon are subjected to isosteric heat analyses; their zero filling isosteric heats of adsorption are consistent with slit‐pore, adsorption energy enhancement modelling. Water adsorbs entirely via specific interactions, offering decreasing isosteric heat at low pore filling followed by a constant heat slightly in excess of water condensation enthalpy, demonstrating the effects of micropores. Methanol offers both specific adsorption via the alcohol group and non‐specific interactions via its methyl group; the isosteric heat increases at low pore filling, indicating the predominance of non‐specific interactions. Abstract : The heat is on : A qualitative interpretation is proposed to interpret isosteric heats of adsorption by considering contributions from three general classes of interaction energy: fluid–fluid heat, fluid–solid heat, and fluid–high‐energy site heat.